Cloud-Based PLTS Technology Education at SMAN 7 South Tangerang: Edukasi Teknologi PLTS Berbasis Cloud di SMAN 7 Tangerang Selatan - Satrio Yudho; Koerniawan, Tony; Hasanah, Aas Wasri; Qosim, M Nur; Sirait, Rummi; Gifson, Albert; Mangapul, Juara (Universitas Lancang Kuning, 2025)
Developing expertise and having competence in the field of renewable energy is a process that must be carried out through formal education, referring to the Decree of the Minister of Education, Culture, Research and Technology of the Republic of Indonesia Number 262/M/2022 concerning the education curriculum that contains renewable energy material only for Vocational High Schools, while High Schools only concentrate on Natural Science material. Solar Power Plants or called PLTS are one of the Power Generation Technologies that work based on the basic principles of Natural Science and Renewable Energy. Understanding the System and characteristics of solar power plants is an important essence to achieve the ability to apply the technology itself. This Community Service activity program aims to improve the understanding of High School students regarding the working system and characteristics of electrical energy produced from a simple PLTS system integrated with Cloud technology. The evaluation results showed that 79.2 percent of participants or students understood the basic principles of energy, PLTS and the use of Cloud Technology. This program supports the Renewable Energy Education curriculum and produces relevant teaching aids for learning